2018
DOI: 10.1016/j.beth.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Homework Completion, Patient Characteristics, and Symptom Change in Cognitive Processing Therapy for PTSD

Abstract: We evaluated the impact of homework completion on change in PTSD symptoms in the context of two randomized controlled trials of Cognitive Processing Therapy for PTSD (CPT). Female participants (n = 140) diagnosed with PTSD attended at least one CPT session and were assigned homework at each session. The frequency of homework completion was assessed at the beginning of each session and PTSD symptoms were assessed every other session. Piecewise growth models were used to examine the relationship between homework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 41 publications
(54 reference statements)
2
32
2
Order By: Relevance
“…Adherence to homework was found to be positively associated with treatment outcome in two studies (Marks, Lovell, Noshirvani, Livanou, & Thrasher, 1998 ) (Dorrepaal et al, 2012 ), but one study found no association with the amount of time spent on completing homework and treatment outcome (Spence et al., 2011 ). Completion of homework was associated with better outcomes for patients with fewer years of formal education compared to those who reported more years of education (Stirman et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Adherence to homework was found to be positively associated with treatment outcome in two studies (Marks, Lovell, Noshirvani, Livanou, & Thrasher, 1998 ) (Dorrepaal et al, 2012 ), but one study found no association with the amount of time spent on completing homework and treatment outcome (Spence et al., 2011 ). Completion of homework was associated with better outcomes for patients with fewer years of formal education compared to those who reported more years of education (Stirman et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Exploratory analyses to determine whether medication change during treatment modified the treatment effect for CAPS severity scores indicated that the interaction between medication change and treatment was not significant. (Spence et al, 2011 ; Stirman et al, 2018 ) USA Cognitive Processing Therapy (CPT). Internet delivered Cognitive Behavioural Therapy (I-CBT) for PTSD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pain and other physical concerns can impede the cognitive functioning necessary for engaging in trauma-focused treatment and challenging maladaptive beliefs (Moriarty & Finn, 2014 ). Poor physical functioning may also interfere with homework compliance (Branch, 2012 ), which has been linked to improved treatment outcome in CPT (Stirman et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Walter et al () reported that lower education was associated with greater improvement in PTSD symptoms during CPT in a veteran sample; however, Rizvi et al () did not detect a relationship between education and outcome. In a recent secondary analysis, education was found to be positively related to homework completion but there was evidence that individuals with less education reported more benefit from the homework (Stirman et al, ). More information is needed regarding these variables and their relationship to PTSD severity and treatment response.…”
Section: Introductionmentioning
confidence: 99%